Penerapan Pembelajaran Berbasis Praktikum Untuk Meningkatkan Keterampilan Proses Sains Dan Sikap Ilmiah Siswa - Yuli Arnita Sari; Anna Fitri Hindriana; Sri Redjeki (Program Studi Pendidikan Biologi, Sekolah Pascasarjana Universitas Kuningan, 2019)
The purpose of this research is to improve the science process skills and students' scientific attitude through the use of practicum-based learning. The method used is quasy experiment. The research design used is Nonequivalent Control-Group Design. Sampling technique of this research using purposive random sampling. Data collection techniques are: test, observation and questionnaire techniques. The research was conducted at one of Vocational High School in Cirebon City, SMK RISE Kedawung Cirebon. The implementation of this practicum-based learning can be fully (100%) implemented. Practicum-based learning is able to improve students' science process skills before the learning (pretest) the average student score is 38.13, while after learning is 85.27. N-Gain obtained in each indicator of science process skill are observation, prediction, and use a tool or material or source are 1 (one); apply the concept, communicate, interpretation are 0.90; to plan an experiment is 0,74; The hypothesized is 0.62. The value of improvement students' science process skill indicator based on the highest observation is the indicator of using the tool or the material or the source 47, and the lowest is indicator 28. Improvement scientific attitudes of students based on the highest is prioritizes the proof indicator 48, and the lowest is the indicator of a positive attitude to failure 28. Practicum-based learning is very good and appropriate to be implemented in the learning process because it can be provide experience and skills in working in laboratory environment carefully and according to the procedureKeywords: Practicum-based learning; Science process skills; Scientific attitude